Analysis of the Effect of the Educational System and Student Motivation in Creating Workforce Competitiveness (A Case Study Facing the Industrial Revolution 4.0) - Zen, Agustian; Sukaesih, Kesih; Malik, Aulia Januar (Technium Social Sciences Journal, 2022)
The purpose of this study was to determine the effect of the Education System and Student Motivation in Creating Labor Competitiveness (A Case Study Facing the Industrial Revolution 4.0. This study used a quantitative analysis method, namely research using the output of the statistical analysis process towards primary data, which is the answer or feedback (feed back) from respondents who collected through a questionnaire (questionair).This research was conducted at Bhayangkara University, Jakarta Raya, Bekasi. The number of samples determined was 87 respondents using purposive sampling method. Data processing techniques using PLS 3.0 tools. Based on the results of the tests that have been carried out, it shows that the indicators are valid and reliable. The coefficient of determination shows the number of 0.352 which means that the variable of Labor Competitiveness is influenced by the Education System and Student Motivation by 67%. The results of the hypothesis test show that the Education System and Student Motivation have a positive and significant effect on the competitiveness of the workforce.